2019
DOI: 10.1017/s0305000919000576
|View full text |Cite
|
Sign up to set email alerts
|

Phonological memory problems are magnified in children from language minority homes when predicting reading disability

Abstract: Children from language minority (LM) environments speak a language at home that differs from that at school, are often from socioeconomically disadvantaged backgrounds, and are at risk for reading impairment. We evaluated the main effects and interaction of language status and phonological memory and awareness on reading disorder in 352 children from socioeconomically disadvantaged backgrounds. A significant phonological memory by language status interaction indicated that phonological memory problems were mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…After objective analysis, 25 factors were utilized for the AHP analysis, as presented in Tables 1-4. These factors were selected by avoiding bias through selection technique [15]. Specifically, this study applied the concept of selection strategy in selecting the factors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…After objective analysis, 25 factors were utilized for the AHP analysis, as presented in Tables 1-4. These factors were selected by avoiding bias through selection technique [15]. Specifically, this study applied the concept of selection strategy in selecting the factors.…”
Section: Literature Reviewmentioning
confidence: 99%
“… Wagner et al (1997) found that PM did not uniquely influence word reading above and beyond PA and RAN skills. However, research has demonstrated that there are differences in reading ability related to PM ( Al Otaiba and Fuchs, 2002 ; Swanson et al, 2009 ; Hardy et al, 2019 ). PM taps short-term memory and has been found to be strongly associated with vocabulary knowledge across the life span ( Gathercole et al, 1999 ).…”
Section: Introductionmentioning
confidence: 99%